FINANCIAL PERFORMANCE IN LIGHT OF KNOWLEDGE MANAGEMENT CORE - Assist Prof. Dr. Majeed Mohsen Mohammad; Krar Muhsin Thajil (Journal Park Publishing, 2023)
The aim of article is to the find the core of knowledge management processes and if that core is represented in financial performance. the knowledge management processes are knowledge Acquisition , knowledge storage, Knowledge disseminating and Knowledge usage. the research did use three dimensions as a core of knowledge management processes they are strategic thinking, innovation and organizational changing. the research question: Is the core of the knowledge management processes are strategic thinking, innovation and organizational changing ? if so is financial performance represented this core?
Keywords: creativity, change, strategic thinking, financial performance.